2017
DOI: 10.1111/jpn.12779
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression differences in the methionine remethylation and transsulphuration pathways under methionine restriction and recovery with D,L‐methionine or D,L‐HMTBA in meat‐type chickens

Abstract: SummaryThis study examined the molecular mechanisms of methionine pathways in meat-type chickens where birds were provided with a diet deficient in methionine from 3 to 5 weeks of age. The birds on the deficient diet were then provided with a diet supplemented with either D,L-methionine or D,L-HMTBA from 5 to 7 weeks. The diet of the control birds was supplemented with L-methionine from hatch till 7 weeks of age.We studied the mRNA expression of methionine adenosyltransferase 1, alpha, methionine adenosyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The minimum point found for glycogen deposition in the liver was 0.348g/100g dMet, estimated by the derivative of the regression equation (Table 5). Methionine plays a role in liver fat metabolism because it is necessary for fat methylation processes, and as consequence of amino acid deficiency, there is accumulation in the liver of the birds, and a relationship between methylation and gene of lipoprotein lipase in birds in nutrient deficiency situations of the sulfur amino acids (Aggrey, González-Cerón, Rekaya, & Mercier, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum point found for glycogen deposition in the liver was 0.348g/100g dMet, estimated by the derivative of the regression equation (Table 5). Methionine plays a role in liver fat metabolism because it is necessary for fat methylation processes, and as consequence of amino acid deficiency, there is accumulation in the liver of the birds, and a relationship between methylation and gene of lipoprotein lipase in birds in nutrient deficiency situations of the sulfur amino acids (Aggrey, González-Cerón, Rekaya, & Mercier, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that MR can protect the integrity of the broiler liver, and this protective effect may be attributed to the liver being the main organ for methionine metabolism. MR increases cystathionine β-synthase (CBS) and cystathionine γ cleaving enzyme (CSE) content in the liver, which promotes the synthesis of glutathione (GSH) and hydrogen sulphide (H 2 S) ( Aggrey et al, 2018 ). Glutathione and H 2 S play antioxidant roles, thus protecting the liver from oxidative damage ( Mou et al, 2020 ; Elwan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, DL-Met and DL-HMTBA activated both remethylation pathways, mainly in conditions of methionine deficiency. While evaluating the duodenum of broilers, some authors observed that when the birds were fed with DL-Met, the choline-betaine pathway was more stimulated, with greater expression of BHMT, while DL-HMTBA stimulated the tetrahydrofolate pathway more, with greater expression of the MTR and MTRR genes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%